A New Voltage Control Method for Single-Phase PWM Inverters - Pekik Argo Dahono; Een Taryana (Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
A new voltage control method for single-phase full-bridge PWM inverters that having an output LC filter is proposed in this paper. The proposed voltage controller has a capability to realize a zero steadystate output voltage error with fast response. The zero steady-state output voltage error is achieved by using a controller that is derived by using the virtual LC resonant circuit. Fast response is obtained by using a virtual resistance that is connected in parallel with the filter capacitor. The validity of the proposed method is verified by experimental results.